The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s11307-007-0088-1
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Imaging Techniques in Neurodegenerative Diseases

Abstract: Neurodegeneration induces various changes in the brain, changes that may be investigated using neuroimaging techniques. The in vivo techniques are useful for the visualization of major changes, and the progressing abnormalities may also be followed longitudinally. However, to study and quantify minor abnormalities, neuroimaging of postmortem brain tissue is used. These in vitro methods are complementary to the in vivo techniques and contribute to the knowledge of pathophysiology and etiology of the neurodegene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 101 publications
(91 reference statements)
0
17
0
Order By: Relevance
“…The latter advantages have allowed the identification in CSF of two novel Ab peptides, Ab2-17 and Ab3-17, proposed to be cleavage products from NEP and ECE (Portelius et al, 2007). MALDI/MS is also a technique often applied to profile the Ab population of other complex samples such as mouse neuroblastoma cells transfected with cDNAs that encode wild-type or mutant human APP (Wang et al, 1996), and it offers also the exclusive advantage of carrying out label-free molecular imaging to allow a simultaneous mapping of multiple analytes in biological tissue sections (Stoeckli et al, 2006;Langstrom et al, 2007). For this reason, a new analytical approach called MALDI/mass spectrometric imaging (MSI) on tissues is already used in biomarker discovery by determining under-and over-expressed peptides/proteins of a disease state versus a healthy control (Rohner, Staab, & Stoeckli, 2005).…”
Section: Detection and Structural Analysis Of Abmentioning
confidence: 99%
“…The latter advantages have allowed the identification in CSF of two novel Ab peptides, Ab2-17 and Ab3-17, proposed to be cleavage products from NEP and ECE (Portelius et al, 2007). MALDI/MS is also a technique often applied to profile the Ab population of other complex samples such as mouse neuroblastoma cells transfected with cDNAs that encode wild-type or mutant human APP (Wang et al, 1996), and it offers also the exclusive advantage of carrying out label-free molecular imaging to allow a simultaneous mapping of multiple analytes in biological tissue sections (Stoeckli et al, 2006;Langstrom et al, 2007). For this reason, a new analytical approach called MALDI/mass spectrometric imaging (MSI) on tissues is already used in biomarker discovery by determining under-and over-expressed peptides/proteins of a disease state versus a healthy control (Rohner, Staab, & Stoeckli, 2005).…”
Section: Detection and Structural Analysis Of Abmentioning
confidence: 99%
“…[8][9][10] Disease studies such as the fundamental understanding of the biochemistry of neurodegenerative diseases 11,12 or cancer, 13 drug distribution studies 10,14 and forensics, 15,16 among others, also benefit from the information revealed by MSI.…”
Section: Introductionmentioning
confidence: 99%
“…However, to study and quantify minor abnormalities, analysis of postmortem brain tissue is necessary (Langstrom et al, 2007). MSI techniques, for example, have been used to compare molecular patterns in prelesion and postlesion areas in different animal models of progressive Parkinson's Disease (PD) (Pierson et al, 2004).…”
Section: Vertebrate Brain Studies With Maldi Msimentioning
confidence: 99%
“…Most antibodies used in immunocytochemical studies for assessing the presence of ubiquitin in PD-associated Lewy bodies are directed toward a protein-bound form of ubiquitin. Free monomeric ubiquitin is not immunogenic in most mammalian species used to produce antibodies (Pierson et al, 2005;Langstrom et al, 2007). These antibodies are also capable of crossreacting with free monomeric ubiquitin, and therefore it is unclear in which form ubiquitin is detected using these immunocytochemical techniques.…”
Section: Vertebrate Brain Studies With Maldi Msimentioning
confidence: 99%
See 1 more Smart Citation